2021
DOI: 10.2169/internalmedicine.6119-20
|View full text |Cite
|
Sign up to set email alerts
|

Healed Erosion: The Role of Pre-interventional Optical Coherence Tomography in a Patient Clinically Suspected of Having Unstable Angina with Coronary Spasm

Abstract: A 46-year-old man complained of chest pain at rest for the past three months. His symptoms gradually exacerbated and were suspected of being due to unstable angina. A coronary angiogram revealed focal tight stenosis at the proximal left anterior descending coronary artery with gross spastic coronary findings. Optical coherence tomography (OCT) revealed layered low-intensity structures with microvessels and the accumulation of macrophages, which indicated progressive stenosis with multiple-layered organized thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In 2017, Shin et al reported that thrombus and plaque erosion were more common at spasm segments than at nonspasm segments 64) . In (2022) reported layered plaque at spasm sites, which was thought to have healed plaque erosion [66][67][68] . In 2020, Wakabayashi et al reported the accumulation of macrophages only in the segment of focal spasm in a case of myocardial infarction with nonobstructive coronary arteries 69) .…”
Section: Yamagishi Et Al Reported the Presence Of Mild Atherosclerosi...mentioning
confidence: 99%
“…In 2017, Shin et al reported that thrombus and plaque erosion were more common at spasm segments than at nonspasm segments 64) . In (2022) reported layered plaque at spasm sites, which was thought to have healed plaque erosion [66][67][68] . In 2020, Wakabayashi et al reported the accumulation of macrophages only in the segment of focal spasm in a case of myocardial infarction with nonobstructive coronary arteries 69) .…”
Section: Yamagishi Et Al Reported the Presence Of Mild Atherosclerosi...mentioning
confidence: 99%